Error Analysis of English Sentences Written by Indonesian College Students - Ahmad Burhanuddin (Jurnal Lingua Idea, 2020)
This study aims to investigate (1) the pattern of the errors made by the Indonesian students (2) the dominant errors (3) the impact of the errors. Designed as qualitative research this research involved 100 students of the second year of the English Department IAIN Pekalongan. The data were collected through an open-ended questionnaire as the instrument of this study. The research findings reveal that (1) the patterns of the errors are spread into eleven types of errors, including verbs, articles, spelling, adjectives, preposition, sentence structure and ordering, word formation, word selection, noun, pronoun, and ambiguous communication; (2) 55.28% of the errors are in terms of subject-verb agreements, the use of articles (9.76 %), and misspelling (8.94%). These findings illustrate that most of the students did not know how to use verb and articles correctly and they need to pay attention to the spelling of the English words; (3) the errors found in the sentences give some ambiguities to the meaning of the sentences.